Analyzing CIM to PIMTransformationsUsing the WRSPM model - Siqueira, Fábio Levy; Silva, Paulo Sérgio Muniz (INFOCOMP Journal of Computer Science, 2012)
Model-Driven Architecture (MDA) is a framework for software development focusing on models and model transformation. One of its models is the computation independent model (CIM), which describes the system environment and requirements. Representing this model and transforming it into a platform independent model (PIM) typically involves Requirements Engineering approaches and diagrams. Although there are some approaches that propose CIM to PIM transformations, it is not clear how Requirements Engineering concepts are related to MDA models. To improve the understanding of MDA and to define which artifacts are expected from a Requirements Engineering perspective in CIM to PIM transformations, this paper analyzes some proposals, found in a survey, and proposes a mapping between a requirements reference model,the WRSPM model, and Model-Driven Architecture models.